2020
DOI: 10.1093/cercor/bhaa224
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation Over the Human Medial Posterior Parietal Cortex Disrupts Depth Encoding During Reach Planning

Abstract: Accumulating evidence supports the view that the medial part of the posterior parietal cortex (mPPC) is involved in the planning of reaching, but while plenty of studies investigated reaching performed toward different directions, only a few studied different depths. Here, we investigated the causal role of mPPC (putatively, human area V6A–hV6A) in encoding depth and direction of reaching. Specifically, we applied single-pulse transcranial magnetic stimulation (TMS) over the left hV6A at different time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 141 publications
(187 reference statements)
2
16
0
Order By: Relevance
“…Fifteen healthy volunteers (6 males; age range 19–33 years; mean age 21.93 ± 4.27 years) participated in this study. The number of participants was determined based on a power analysis that indicated that a sample size of 15 participants is an appropriate sample size to achieve statistical power (1−β) of 0.95 (2-tailed α = 0.05; effect size f = 0.20, Breveglieri et al. 2021 ), analysis performed using G*Power software ( Faul et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen healthy volunteers (6 males; age range 19–33 years; mean age 21.93 ± 4.27 years) participated in this study. The number of participants was determined based on a power analysis that indicated that a sample size of 15 participants is an appropriate sample size to achieve statistical power (1−β) of 0.95 (2-tailed α = 0.05; effect size f = 0.20, Breveglieri et al. 2021 ), analysis performed using G*Power software ( Faul et al.…”
Section: Methodsmentioning
confidence: 99%
“…The coordinates of hV6A are the same as those used in previous TMS studies on this brain region ( Ciavarro et al. 2013 ; Breveglieri et al. 2021 ) and are similar to those used for studying the SPOC ( Vesia et al.…”
Section: Methodsmentioning
confidence: 99%
“…The parietal lobes integrate visual data from rapid eye movements (saccadic movements) to direct the mechanistic reaching movements of the hand, allowing the individual to place an object in space and reach out to grasp it [88,92]. However, when the parietal cortex is impaired, depth perception cannot function properly, causing loss of the ability to perceive the spatial layout of the objects surrounding them [93]. Another consequence of parietal lobe dysfunction occurs in patients who lose the ability to shift their spatial attention or distinguish things on their left or their right side, leading to difficulty navigating even simple tasks such as walking across a room [90,94].…”
Section: Tbi Affects the Parietal Lobes Vestibular System And Visual ...mentioning
confidence: 99%
“…The Talairach coordinates of hV6A we used were x = −10, y = −78, and z = 40 [49]. These coordinates are the same as those used in two previous TMS studies on hV6A [50,51], and are similar to those used for studying area SPOC [12,52], a region also investigated in imaging studies [8,10,53] that likely includes hV6A [54]. Then, the neuronavigation system was used to estimate the projections of scalp sites on the brain surface.…”
Section: Localization Of Brain Sitesmentioning
confidence: 99%